Tuberculous lymphadenitis – still on the scene: a case report - Milić, Rade; Šarac, Sanja; Lazović-Popović, Biljana; Vasiljević, Mira; Šarac, Momir (Vojnosanitetski pregled, 2025)
Introduction. Tuberculosis (TB) continues to be a global health problem, with various manifestations affecting different organs and organ systems. Tuberculous lymphadenitis (TBL), also known as scrofula or lymph node (LN) TB, is a manifestation of Mycobacterium tuberculosis infection primarily affecting the LNs. Our region has a low annual incidence rate of TB, which is why the expected prevalence of TBL is also low. Case report. We present two cases of TBL diagnosed three months apart. Both presented patients had the disease localized in the LNs of the neck. These were young people without chronic diseases and previously in good health condition. The diagnosis was confirmed by surgical biopsy of the LNs in the first patient and fine needle aspiration biopsy in the second patient. Both patients were treated with standard protocols for TBL, with favorable outcomes and without significant complications and side effects. Conclusion. Presented cases highlight the importance of considering TBL in the differential diagnosis of neck masses, even in regions with a low prevalence of TB. Timely diagnosis and treatment are essential for preventing complications and ensuring a successful outcome.
Keywords: biopsy; biopsy, fine-needle; diagnosis, differential; drug therapy; lymphadenitis; neck; tuberculosis; treatment outcome.